The use of streamlined LCA for the environmental assessment of plastics recycling: the case of a PVC container - Georgakellos, Dimitrios A. (SPOUDAI Journal of Economics and Business, 2005)
The problem of disposal of plastic wastes due to declining landfill capacity, together with the polluting emissions when thermal treatment is involved, has encouraged plastics recycling. Recycle strategies for plastic-based products can be yield significant environmental benefits. However, these strategies have also been criticized because of their possible links to other types of resource and environmental impacts. The purpose of the present paper is to identify and quantify the environmental effect of recycling of a PVC container. For this evaluation, the methodology of Life Cycle Assessment (LCA) is used, and especially its version of Streamlined LCA. According to the results of this analysis, recycling can substantially reduce the environmental burden of the container in question JEL Classification: Q20, L60